PENGARUH PER EPS ROA DAN DER TERHADAP HARGA SAHAM LQ45 DI BURSA EFEK INDONESIA - Puput Rarindra Adi Saputra (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
Effect of PER, EPS, ROA, and DER towards LQ45 share price in the Indonesia Stock Exchange. Under the guidance of Dr. Makmur, SE., M.SI as Supervisor I and Mr. Eko A. Widyanto, SE., M.SA as Advisor II. This study aims to determine the effect of variable PER, EPS, ROA, and DER towards LQ45 share price in the Indonesia Stock Exchange. Data collection techniques are the methods of documentation. For testing instrument using classical assumption test and test statistics. As for the technique of data analysis using multiple linear regression for the variables used four variables, the F test and t test. The results showed that the variables PER (X1), EPS (X2), ROA (X3) and DER (X4) simultaneously significant effect on stock prices LQ45 Indonesian Stock Exchange Securities (Y). Analysis result simultaneously can explaine that EPS ratio take positive effect and significant on stock prices LQ45 in Indonesia Stock Exchange.